Sistem Pendidikan Islam di Mesir Pada Zaman Modern - Padila, Cisia; Ikhsan, Ramadhanul; Amanah, Tegu Reski; Erman, Erman; Hasnah, Radhiatul (An-Nuha, 2023)
Islamic civilisation entered the modern era in the 1800s and continues to develop today, marked by various revival movements in various fields. In the education sector, this progress was reflected through various endeavours, such as the establishment of the Ministry of Education and public educational institutions, sending Egyptian students to study in Europe, and efforts to improve access to education. In the field of civilisation, progress was seen in the fields of architecture, literature, and the art of calligraphy. This research utilises the historical research method, which specifically involves the interpretation of a historical period to understand its historical context. The data collection process involved the acquisition of a wide range of relevant sources and data, focusing on documents, scholarly literature, and other writings relating to the relationship between the Muslim and Christian worlds, from the Middle Ages to the modern era